Cultivo de couve-flor em função da utilização de água residuária, sistemas de gotejamento e coberturas do solo - (:unkn) unknown (Universidade Estadual de Goiás, 2012)
Population growth, the expansion of agriculture, industry, environmental degradation, availability and poor water distribution, motivate the reuse of water for agricultural purposes especially in cultures that are not eaten raw. The aim of this study was to evaluate the development of the culture of cauliflower irrigated by surface and subsurface drip fertigation using wastewater as different cover crops. The experiment was conducted at the State University of Goiás-UnUCET between the months of April to July 2012 in Anapolis, Goias The experiment was conducted in a factorial 2 x 2 x 3 randomized block design with three replications, totaling 36 plots , 2 types of water, 2 types of drip irrigation systems and 3 types of ground cover. The experimental plots (treatments) are the water (deep well of natural and wastewater), irrigation systems (surface and subsurface drip) and cover crops (Mulching, TNT and bare soil). To check the quality of wastewater and natural water, we analyzed the following parameters: pH, electrical conductivity, temperature, dissolved oxygen, turbidity. For quantitative analyzes of wastewater were analyzed further: nitrate, nitrite, ammonia, potassium, manganese, total phosphate, sodium, total iron, ferro2+, ferro3+, total hardness, calcium hardness, magnesium, calcium, magnesium, COD, BOD, total solids, total coliform and Escherichia coli. As a way of analyzing culture we used the following parameters: plant leaf area, plant height, leaf chlorophyll content, number of leaves per plant, inflorescence weight, transverse diameter of the inflorescence and the inflorescence microbiological analysis to check for possible contamination. Irrigation systems were evaluated for application efficiency and distribution of the water. The tension of water in the soil was determined by a digital tensiometer puncture. Data were subjected to analysis of variance by F test at 5% significance and where relevant realized the Tukey test for comparison of means with the same level of significance. The most significant results indicated the interaction between types of water system and surface drip irrigation were most influenced variables. The use of wastewater resulted in commercial nutrient economy. The indices of uniformity of distribution of the drip irrigation water at the beginning and end of the cycle were excellent in all treatments. The tension of water in the soil was maintained within acceptable range for the cultivation of cauliflower. The wastewater can be applied as fertigation in the production of cauliflower.
Keywords: Fertirrigação; Mulching; TNT; Brassica Oleracea var; Botrytis; Fertigation; Mulching; TNT; Brassica oleracea var; Botrytis; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA; ENGENHARIA DE AGUA E SOLO::IRRIGACAO E DRENAGEM; ENGENHARIA SANITARIA::SANEAMENTO AMBIENTAL